Balancing risk and professional identity, secondary school teachers' narratives of violence. (September 2013) - Martin, Denise; Mackenzie, Nicola; Healy, Jane
Violence against teachers is seen as a growing problem by both professional bodies and the media. However, this account fails to acknowledge differing views about what actually constitutes violence and how those that experience violence comprehend it. Drawing on literature on workplace violence and fear of crime, this article seeks to identify how we can begin to understand better violence against teachers. Furthermore, by examining secondary school teachers' own narratives in depth, it is identified that a number of factors influence the meanings that they attach to their own experiences of workplace violence. This includes their professional identity, feelings about their pupils and their role as a teacher, their own sense of vulnerability, levels of experience and general feelings about schools and young people today.